ANALISIS NILAI KEKELUARGAAN DALAM NOVEL DOMPET AYAH SEPATU IBU KARYA J.S KHAIREN DENGAN PENDEKATAN SOSIOLOGI SASTRA - Yoga Juliani; Elsa Mulya Karlina (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
The research Analysis of Family Values in the Novel Dompet Ayah Sepatu Ibu by J.S. Khairen with a Literary Sociology Approach aims to describe the representation of family values in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen, using a literary sociology approach. The research problem is how the representation of family values in the novel Dompet Ayah Sepatu Ibu by J.S. Khairen. To get the results of the research using descriptive qualitative methods with the type of library research. With the use of the theory of family values by Dunst, Trivette, the results show that the novel Dompet Ayah Sepatu Ibu by J. S Khairen contains family values. S Khairen's Novel Dompet Ayah Sepatu Ibu by J. S. Khairen contains familial values including, believing and committing to the improvement of the welfare and development of members in the family, rules, values, beliefs and behaviors that should not and can be accepted, sticking to life goals when things are good or difficult, sharing responsibilities, respecting personal rights between family members, having family traditions or special rituals, believing in the importance of being active and learning new things, believing that all problems can be resolved when the whole family works together, considering loyalty and integration in the family.